Neural substrates of contingency learning and executive control: dissociating physical, valuative, and behavioral changes - Mullette-Gillman, O'Dhaniel A.; Huettel, Scott A. (Frontiers in Human Neuroscience, 2009)
Contingency learning is fundamental to cognition. Knowledge about environmental contingencies allows behavioral flexibility, as executive control processes accommodate the demands of novel or changing environments. Studies of experiential learning have focused on the relationship between actions and the values of associated outcomes. However, outcome values have often been confounded with the physical changes in the outcomes themselves. Here, we dissociated contingency learning into valuative and non-valuative forms, using a novel version of the two-alternative choice task, while measuring the neural effects of contingency changes using functional magnetic resonance imaging (fMRI). Changes in value-relevant contingencies evoked activation in the lateral prefrontal cortex (LPFC), posterior parietal cortex (PPC), and dorsomedial prefrontal cortex (DMPFC) consistent with prior results (e.g., reversal-learning paradigms). Changes in physical contingencies unrelated to value or to action produced similar activations within the LPFC, indicating that LPFC may engage in generalized contingency learning that is not specific to valuation. In contrast, contingency changes that required behavioral shifts evoked activation localized to the DMPFC, supplementary motor, and precentral cortices, suggesting that these regions play more specific roles within the executive control of behavior.